2021
DOI: 10.1371/journal.pone.0254821
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among healthcare workers and other vulnerable groups during the COVID-19 pandemic and other coronavirus outbreaks: A rapid systematic review

Abstract: Introduction Although most countries and healthcare systems worldwide have been affected by the COVID-19 pandemic, some groups of the population may be more vulnerable to detrimental effects of the pandemic on mental health than others. The aim of this systematic review was to synthesise evidence currently available from systematic reviews on the impact of COVID-19 and other coronavirus outbreaks on mental health for groups of the population thought to be at increased risk of detrimental mental health impacts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 31 publications
5
65
0
2
Order By: Relevance
“…Though it has been demonstrated that the trend of contagion has differently affected the mental health status of HCWs working in areas with dissimilar incidences of COVID-19 cases [ 23 , 24 ], it is also true that regional differences in stress perception and coping strategies also depend on cultural factors, home/work interface, social support, and economic environment [ 25 , 26 ]. In a Chinese study, comparing subjects coming from Hubei and from non-endemic provinces, health workers in the endemic region showed lower anxiety levels about the COVID-19 epidemic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Though it has been demonstrated that the trend of contagion has differently affected the mental health status of HCWs working in areas with dissimilar incidences of COVID-19 cases [ 23 , 24 ], it is also true that regional differences in stress perception and coping strategies also depend on cultural factors, home/work interface, social support, and economic environment [ 25 , 26 ]. In a Chinese study, comparing subjects coming from Hubei and from non-endemic provinces, health workers in the endemic region showed lower anxiety levels about the COVID-19 epidemic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…The literature on healthcare workers during pandemic has highlighted several issues, the key of them are connected with a lack of evidence on interventions for vulnerable groups, healthcare staff in particular (Uphoff et al, 2021). The findings of this research show that personal factors, the work environment, and social networks for mental health are the key risk-and protective factors in healthcare staff.…”
Section: Introductionmentioning
confidence: 83%
“…37 Identified risk factors such as female gender, younger age, being a first-line healthcare worker, living in urban areas, having lower income and worse self-reported health status agree with the literature. 38 As for the respondents' knowledge and perceptions towards the new coronavirus, the vast majority acknowledged that the virus may be asymptomatic and that it is dangerous for older people and for those with underlying health problems. Furthermore, almost two thirds of respondents agreed with its airborne transmission although this topic was still controversial among researchers by that time with some data supporting this mode of transmission, [39][40][41] while other studies did not.…”
Section: Discussionmentioning
confidence: 99%